"A Ritz Among Laundrettes": Identities and New Waves in My Beautiful Laundrette. Issue 3 (23rd March 2023) - Fergusson, Emma
This article analyzes the 1985 Stephen Frears-directed film, My Beautiful Laundrette, as a precursor to the New Queer Cinema movement, and as significant for its portrayal of characters with complex, intersectional identities, living in Thatcher's England. The laundrette at the film's center serves as a space in which its characters can find success in business and the freedom to live out their sexuality, but which nonetheless remains inextricable from the oppressive society that surrounds. Furthermore, I investigate the stylistic impact of the film's origins in television.